2012
DOI: 10.1021/ma301691f
|View full text |Cite
|
Sign up to set email alerts
|

Precision Synthesis of Narrow Polydispersity, Ultrahigh Molecular Weight Linear Aromatic Polymers by A2 + B2 Nonstoichiometric Step-Selective Polymerization

Abstract: Cycloaddition. -Significant amounts (20-45% NMR) of undesired regioisomers are also generated in some cases. -(MORI, A.; ARAKI, T.; MIYAUCHI, Y.; NOGUCHI, K.; TANAKA*, K.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
110
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 39 publications
4
110
0
Order By: Relevance
“…Although it has been proposed that superacid catalyzed polyhydroxyalkylations deviate significantly from the classical behavior of A 2 + B 2 step‐growth polymerizations, there are no kinetic modeling studies, focused on molecular weight development, reported for this system, which can explain such deviations. It is our objective in this contribution to propose a kinetic model for superacid catalyzed polyhydroxyalkylations focused on molecular weight development.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although it has been proposed that superacid catalyzed polyhydroxyalkylations deviate significantly from the classical behavior of A 2 + B 2 step‐growth polymerizations, there are no kinetic modeling studies, focused on molecular weight development, reported for this system, which can explain such deviations. It is our objective in this contribution to propose a kinetic model for superacid catalyzed polyhydroxyalkylations focused on molecular weight development.…”
Section: Introductionmentioning
confidence: 92%
“…Zolotukhin and co‐workers developed a superacid catalyzed polyhydroxyalkylation novel synthetic route (see Figure ), which can be classified as an unusual A 2 + B 2 step‐growth polymerization since ultrahigh molecular weights and molar mass dispersities ( Ð ) less or higher than two are possible, at nonstoichiometric conditions. The dramatic acceleration in polymerization rate observed in superacid catalyzed polyhydroxyalkylations with a small excess of the carbonyl compound is known as the “nonstoichiometric effect.” Superacid catalyzed polyhydroxyalkylations have the following advantages: (i) the reaction proceeds at room temperature and atmospheric pressure, (ii) structural variety and commercial availability of monomers, (iii) high conversion yields, (iv) high regioselectivities, (v) acceptable reaction times, (vi) great versatility in polymer architectures, (vii) functional groups that allow polymer chemical modification reactions, (viii) easy polymer purification, (ix) good physical, chemical, and thermal properties of the produced polymers, and (x) high polymer molecular weights.…”
Section: Introductionmentioning
confidence: 99%
“…Super acidcatalyzed reactions have the following advantages: the reaction proceeds at room temperature, structural selection and easy availability of monomers, high yields and selectivity, short duration of reaction, more versatility in polymer architectures, easy purification, possessing good physical, chemical, and thermal properties of the synthesized polymers, and high molecular weights, etc. [25][26][27]. The perception and explanation of super acid-catalyzed reactions were made by Olah in 1970 [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…We are now exploring other polymers for membrane preparation with stability at extreme conditions. During the last decade, a new family of high performance polymers [32][33][34], based on the superacid condensation of isatin and different arylene monomers have been prepared and studied. Poly(oxindolebiphenylylene) dense films were evaluated for gas separation [35] and fuel cells [36].…”
Section: Introductionmentioning
confidence: 99%